Frequency doubling technique perimetry and spectral domain optical coherence tomography in patients with early glaucoma - Horn, Folkert; Mardin, C. Y.; Bendschneider, D.; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Eye, 2011)
PurposeTo assess the combined diagnostic power of frequency-doubling technique (FDT)-perimetry and retinal nerve fibre layer (RNFL) thickness measurements with spectral domain optical coherence tomography (SDOCT).MethodsThe study included 330 experienced participants in five age-related groups: 77 'preperimetric' open-angle glaucoma (OAG) patients, 52 'early' OAG, 50 'moderate' OAG, 54 ocular hypertensivepatients, and 97 healthy subjects. For glaucoma assessment in all subjects conventional perimetry, evaluation of fundus photographs, FDT-perimetry and RNFL thickness measurement with SDOCT was done. Glaucomatous visual field defects were classified using the Glaucoma Staging System. FDT evaluation used a published method with casewise calculation of an 'FDT-score', including all missed localized probability levels. SDOCT evaluation used mean RNFL thickness and a new individual SDOCT-score considering normal confidence limits in 32 sectors of a peripapillary circular scan. To examine the joined value of both methods a combined score was introduced. Significance of the difference between Receiver-operating-characteristic (ROC) curves was calculated for a specificity of 96%.ResultsSensitivity in the preperimetric glaucoma group was 44% for SDOCT-score, 25% for FDT-score, and 44% for combined score, in the early glaucoma group 83, 81, and 89%, respectively, and in the moderate glaucoma group 94, 94, and 98%, respectively, all at a specificity of 96%. ROC performance of the newly developed combined score is significantly above single ROC curves of FDT-score in preperimetric and early OAG and above RNFL thickness in moderate OAG.ConclusionCombination of function and morphology by using the FDT-score and the SDOCT-score performs equal or even better than each single method alone.
EVALuna2:5300